Persepsi Pelajar terhadap Pemanfaatan Penggunaan Aplikasi Nearpod sebagai Media Pembelajaran di Kelas Rendah: Penelitian - Aulia Fajar Khasanah; Devi Rusiana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
With increasingly sophisticated technological changes and the availability of various digital-based learning media, teachers are required to have a creative and innovative attitude to provide learning to students. This study uses a qualitative descriptive approach. Data obtained through interviews and observations. The purpose of this study is to determine students' perceptions regarding the use of the nearpod application in learning in lower classes, namely class III SDN Srigan 1 Paron. The results of the perception are divided into 2 categories, namely: 1) in students' perceptions about themselves in participating in class learning using the nearpod application, there are many who perceive it as fun and very helpful in understanding the subject matter in order to increase the value of students' knowledge or skills, but there are also those who feel uncomfortable if the use of the nearpod application is disturbed by the internet network during learning; 2) in students' perceptions regarding learning without using the nearpod application media during learning, there are many students who have unpleasant perceptions and feel bored. This makes students less enthusiastic or active during learning.